Formulation Study of a Poly(amino methacrylate) Film-Forming Solution for Transdermal Administration - Chiara G. M. Gennari; Antonella Casiraghi; Francesca Selmin; Francesco Cilurzo (Pharmaceutics)
Background/Objectives: The objective of this paper is to design a novel film-forming system (FFS) based on Eudragit® E PO (EuE) polymeric solutions, differing in volatile solvents (i.e., isopropanol and ethanol) and plasticizers (i.e., tributylcitrate, glycerine, triacetin and PEG 400). Methods: The physicochemical and mechanical properties of the FFS and dried films were evaluated in terms of formation time, stickiness, Tg, tensile strength, break elongation and Young’s modulus. The in vitro skin permeation studies were conducted on formulations containing caffeine and testosterone. Results: The FFS, consisting of EuE and PEG400 in isopropyl alcohol and ethanol (80:20, v/v), exhibited rapid film formation within about 5 min and the dried film allowed a high skin permeability compared to other formulations due to the ability to increase the thermodynamic activity of both drugs. When triiodothyronine (T3) was loaded as a model of a very low soluble drug, tocopherol polyethylene glycol succinate (TPGS) was added as a co-solvent and it allowed for the improvement of T3 retention in the skin. Conclusions: Among the formulative variables, the nature and the amount of plasticizer represent the most critical variables to obtain an EuE-based film with satisfying physical and biopharmaceutical properties.